1997
DOI: 10.1007/bf02551419
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of microsurgical drainage for idiopathic varicocele

Abstract: The long-term results of microsurgical shunts for idiopathic varicocele are reported in the present paper. Sixty-two patients with a total of 65 varicoceles (three were bilateral) were followed up for 1 to 8 years. Pre- and postoperative ultrasonographic evaluation of varicocele size was considered of great importance in order to reduce the bias of subjective clinical diagnosis and to achieve a reliable and objective follow-up. Microsurgical shunts were tailored to the type of reflux: renospermatic (76.9%), il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The main characteristics of the included studies are shown in Table 2 [ 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 …”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are shown in Table 2 [ 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 …”
Section: Resultsmentioning
confidence: 99%
“…In fact, in the peripubertal period, in addition to eliminating the venous stasis, it is also useful to ensure that the testis completes its development with optimal arteriovenous vascularisation (5,6,9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the elimination of venous stasis and the maintenance of good arterial vascularisation, the testicle can complete its de-velopment in an optimal fashion (5,6,9). One of the criticisms which has invariably been brought against this type of operation has to do with the dubious long-term patency of the anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 Besides ligation, another method that has been described in the literature is microsurgical venous bypass between the internal spermatic vein and saphenous or inferior epigastric vein. [7][8][9][10][11][12][13] This method has excellent long-term results, especially in pediatric patients with testicular hypotrophy. 14 The idea behind the bypass is to ligate and reroute the main internal spermatic vein toward the femoral or iliac vein.…”
Section: Introductionmentioning
confidence: 99%
“…The testicular vein to saphenous vein bypass has fallen out of favor because it requires a relatively long and awkward incision (around 8 cm) from the suprascrotal area to the fossa ovalis, or two separate incisions. [11][12][13] The testicular vein to inferior epigastric vein bypass is a good method with excellent results, [7][8][9][10] but has several drawbacks such as longer incision than for simple microsurgical ligation, division of transverse fascia, and the fact that the type of bypass depends on the type of varicocele (according to Coolsaet). Coolsaet demonstrated that in 80 to 90% of patients varicocele is caused by reflux from the left renal vein into the internal spermatic vein (type I varicocele), and in the remaining 10 to 20%, it is due to either the reflux from the left iliac vein into the external spermatic vein (type II varicocele), or a combination of the two (type III varicocele).…”
Section: Introductionmentioning
confidence: 99%